What's Connectionism got to do with IT?! - Abolfazlian, A. R. Kian (DAIMI Report Series, 1994)
In this paper, I shall prove, why the old fashioned Artificial Intelligence cannot be the right answer. Keywords: GOFAI, Fodor, Pylyshyn, Connectionism, Turing machines, Turing-undecidability, Universal Turing machines.